Quản lí công tác xã hội hóa giáo dục ở các trường trung học cơ sở huyện Phú Lộc, tỉnh Thừa Thiên Huế: thực trạng và một số khuyến nghị - Nguyễn , Cao Lãnh (Tạp chí Giáo dục, 2024)
Socialization of education is a correct and long-term policy of the Party, the State and the Education sector to mobilize and organize the widespread participation of organizations, social groups and people to jointly build community responsibility, expand investment sources, exploit the potential of human, material and financial resources in society for education. However, the socialization of education in many localities and units has not been effective. This article presents the results of a survey on the current situation of educational socialization management in secondary schools in Phu Loc district, Thua Thien Hue province. The survey results are an important practical basis to help develop management measures to improve the quality of this work, making an important contribution to promoting the quality of local education and training.